DAMPAK MODAL, DAYA KERJA, DAN BAHAN PEMBUATAN TERHADAP PENGHASILAN INDUSTRI KAIN TENUN PAGATAN - Novia Ardana; Siti Mutmainah Zulfaridatulyaqin (PPJP Universitas Lambung Mangkurat, 2020)
This research was conducted on (1)materials on the income of small woven fabric industry; (2) Discover out which variables are the most prevalent affecting the income of small woven fabric section.The focus of this analysis occupies the field of case study in Kusan Hilir District, Tanah Bumbu Regency. Sources of evidensi in the format of existing evidensi acquired Multilinear estimation will be represented by interviews and questionnaires testing to be checked (simultaneously) and t (partially) through the f method.The findings of the study imply that money, Production and manufactured goods affect benefit positively and significantly of the wood furniture industry either individually (partially) or jointly (simultaneously). Raw material is the most primary factor influencing the wood-furniture industry's profits.Keyword : Investment, Basic Materials , Human Resource, Income